Quality of life after reconstructive surgery for intestinal fistulas - Kaška, Milan; Chobola, Milan; Skalská, Hana; Maňák, Jan; Sobotka, Luboš (Acta Medica, 2018)
BACKGROUND: This retrospective clinical study would like to objectively denote a quality of life of persons afflicted by an abdominal catastrophe and managed by an extensive surgery can be almost as well conformable as those of healthy people in a similar age group. METHODS: A set of eighteen patients who were successfully surgically treated and cured enjoyed a relatively good convalescence after their surgery and returned to a satisfactory standard of life from the point of view of organ function and psychosomatic state. Statistical analysis of the data collected over a period of 1 to 6 years after this complex therapy using special questionnaire for QOL assessment SF-36 was performed. RESULTS: Almost half of the patients evaluated their state similarly to the rest of the population of comparable age and general health status. The remainder of the patients declared significantly worse evaluations in the majority of the observed domains of the questionnaire. CONCLUSION: Therapy of these patients was and must be complex: it included preparation for surgery at a special metabolic internal site, careful diagnostics of the digestive tract state, suitable surgery and good quality care after the surgery.
Keywords: Digestive System Surgical Procedures; lidé; Middle Aged; Adult; Female; průzkumy a dotazníky; retrospektivní studie; Quality of Life; Humans; střevní píštěle; lidé středního věku; chirurgie trávicího traktu; mužské pohlaví; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; kvalita života; Aged; Male; Plastic Surgery Procedures; Retrospective Studies; dospělí; Intestinal Fistula; zákroky plastické chirurgie; Surveys and Questionnaires; senioři